TEMPERATURE EFFECTS ON THE ANT AGONISTIC ACTIVITY OF FUNGAL AND BACTERIAL ANTAGONISTS AGAINST ISOLATES OF FUSARIUM OXYSPORUM AND F. SOLANl - B. KUMAR, I. J. KAPOOR and (Indian Phytopathology, 2002)
Aspergillus fischeri and an isolate of Bacillus sp. (BM-l) caused maximum inhibition of tomato wilt pathogens, Fusarium oxysporum and F. solani under in·vitro conditions. Fungal and bacterial antagonists expressed clear antagonistic activity in the temperature regimes of 20·27°C and 20·25°C, respectively, but were most effective at lowest temperature (20°C) tested. In general, antagonistic activities decreased with an increase in temperature. F. solani isolate KHFs-4I and F. oxysporum isolate D Fo-13 were most sensitive to fungal and bacterial antagonists, respectively.